Early Cambrian Anabarella plana from Three Gorges area, South China - Qiang, Yaqin; Peng, Jiaxin; Song, Zuchen; Sun, Jie; Zhao, Xiaofang; Li, Guoxiang; Han, Jian; Guo, Junfeng (Frontiers in Earth Science, 2023)
Anabarella, a conspicuous taxon of early mollusc, is widely distributed in the early Cambrian strata and is considered an important link in the evolutionary lineage that reflects a transitional form from helcionelloids to bivalves. In South China, Anabarella has mainly been documented from Yunnan, Shaanxi, Sichuan, and Hubei provinces. However, the taxonomy of Anabarella is questionable, which has implications for the interpretation of the genus’ temporal and spatial distribution. New and abundant well-preserved specimens of the helcionelloid mollusc Anabarella were recovered from the Member 5 of the Yanjiahe Formation in the Three Gorges area. Through morphological study, these specimens can be definitely identified as A. plana. On the basis of this new material, the species of Anabarella previously reported in the literature from South China were taxonomically revised, and, with the exception of A. plana from the Yanjiahe Formation, other species should be assigned to Igorella. Therefore, at present, A. plana is the only valid species of the genus Anabarella in South China and is limited to Cambrian Stage 2. Study of the available specimens of A. plana reveal three types of microstructures: convex polygonal impressions, concave polygons, and lamello-fibrillar microstructure. In addition, the thicker shell of the sub-apical area and the three different structures of the sub-apical area provide more evidence that A. plana might have adapted a semi-infanual mode of life and indicate that Anabarella is a likely ancestor of Watsonella.